Emergency ambulance service involvement with residential care homes in the support of older people with dementia: an observational study - Amador, Sarah (BioMed Central, 2014)
BACKGROUND: Older people resident in care homes have a limited life expectancy and approximately two-thirds have limited mental capacity. Despite initiatives to reduce unplanned hospital admissions for this population, little is known about the involvement of emergency services in supporting residents in these settings. METHODS: This paper reports on a longitudinal study that tracked the involvement of emergency ambulance personnel in the support of older people with dementia, resident in care homes with no on-site nursing providing personal care only. 133 residents with dementia across 6 care homes in the East of England were tracked for a year. The paper examines the frequency and reasons for emergency ambulance call-outs, outcomes and factors associated with emergency ambulance service use. RESULTS: 56% of residents used ambulance services. Less than half (43%) of all call-outs resulted in an unscheduled admission to hospital. In addition to trauma following a following a fall in the home, results suggest that at least a reasonable proportion of ambulance contacts are for ambulatory care sensitive conditions. An emergency ambulance is not likely to be called for older rather than younger residents or for women more than men. Length of residence does not influence use of emergency ambulance services among older people with dementia. Contact with primary care services and admission route into the care home were both significantly associated with emergency ambulance service use. The odds of using emergency ambulance services for residents admitted from a relative’s home were 90% lower than the odds of using emergency ambulance services for residents admitted from their own home. CONCLUSIONS: Emergency service involvement with this vulnerable population merits further examination. Future research on emergency ambulance service use by older people with dementia in care homes, should account for important contextual factors, namely, presence or absence of on-site nursing, GP involvement, and access to residents’ family, alongside resident health characteristics.